Enhancing Learning Motivation of Grade XI.9 Students Through Zep Quiz Media in Civics Education at SMA Negeri 3 Palembang - Julia, Julia; Chotimah, Umi; Masito Mutiara, Tyas (Jurnal Profesi Pendidikan, 2025)
The low learning motivation of students during the Pancasila Education learning process motivated this research. The study was caused by students feeling bored due to the use of monotonous and unvaried learning media. The aim of this study was to increase students' learning motivation in the Pancasila Education subject through the use of Zep Quiz media. This research was conducted in the form of Classroom Action Research (CAR), which consisted of two cycles. Each cycle consisted of one meeting that included four stages: planning, implementation, observation, and reflection. The research involved 37 students as the research subjects, specifically from class XI.9 of SMA Negeri 3 Palembang. The study employed two data collection techniques: observation and documentation. The results showed an increase in students' learning motivation from 43% in the pre-cycle, then increasing to 68% in cycle I, and rising again to 88% in cycle II, reaching the "Very Good" category. Thus, the use of Zep Quiz media proved to be effective in enhancing students' motivation in learning Pancasila Education.